The Populist phenomena and the reasons for their success in Hungary - Glied Viktor (Sciendo, 2020)
After the parliamentary elections in 2014, the weakened legitimacy of the Hungarian government could be re-established through activism in migration issues. Fidesz-KDNP that won elections twice already highlighted migration as the main theme of governance from 2014 to 2018, suppressing every other topic on the political agenda. The position that was established for purposes of the Hungarian domestic situation and politics initially faced intense rejections all over Europe, but then garnered some supporters as well, mostly in post-socialist Central and Eastern Europe, and to a smaller extent among the right-wing and populist parties of Western Europe. The anti-refugee and populist approach caused significant success in the communication field to the subscribing parties and governments, and also legitimised Hungarian government’s efforts that could mean it met the majority of the Hungarian society’s expectations. The most essential question is that how can political science reshape its terms and thoughts on populism to understand this phenomenon better, moreover what are the reasons of populism and why is the populist propaganda such successful in Hungary and Eastern Europe.